2020
DOI: 10.34091/ajls.3.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Load, Coliform and Aflatoxins in Wheat Flour of Lahore Metropolitan City

Abstract: In Pakistan, wheat flour is mostly utilized for making flat breads locally called chapattis. Other uses of wheat flour are in bakery products manufacturing. It is an important constituent of daily diet of people. Shelf life of wheat flour is one of the most important factors for its quality determination. Wheat flour is often tainted with pathogenic fungal species and their toxic secondary metabolites called Mycotoxins. The present study was designed to make a comparative analysis of Microbiological quality (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…2. b-Fungal identification: Pure cultures seven days old were identified at the genus or species level was carried out according to the cultural and morphological characters with the help of available literature found principally in publications by [27] for the genus Aspergillus, [5] for the genera of imperfect [29] for Aspergillus and Penicillium). The frequency of identified fungal species was calculated according to the number of isolates of a genus or species/total number of fungal isolates x 100.…”
Section: -Mycoflora Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…2. b-Fungal identification: Pure cultures seven days old were identified at the genus or species level was carried out according to the cultural and morphological characters with the help of available literature found principally in publications by [27] for the genus Aspergillus, [5] for the genera of imperfect [29] for Aspergillus and Penicillium). The frequency of identified fungal species was calculated according to the number of isolates of a genus or species/total number of fungal isolates x 100.…”
Section: -Mycoflora Analysismentioning
confidence: 99%
“…Also, [11] isolated and identified several fungal species associated with corn flour as Aspergillus spp., A. flavus, A. niger, A. terreus, and Penicillium spp. [29] tested some food grains and grain flour market samples. They found that contamination of aflatoxin B 1 was 68.18% in food grains, whereas 100% in grain flour, possibly due to improper post-harvest technology and storage conditions.…”
Section: -Fungal Frequency Occurredmentioning
confidence: 99%
See 1 more Smart Citation